Clinical Profile of Hypertension in Diabetes Mellitus Patients at Surya Melati Muhammadiyah Hospital, Kediri, Indonesia, in 2021 - Ahmad Zaidan Ni'am Abu Adha; Fahmi Adi Priyantoro (Universitas Airlangga, 2025)
Highlights: This study presented the clinical profile of hypertension in patients with DM, providing regional data not previously reported in the literature. It emphasizes the value of implementing targeted interventions. Discussion of pathophysiological mechanisms explained the link between DM and hypertension. Abstract Introduction: The cardiologic and vascular consequences of both diabetes mellitus (DM) and hypertension often occur side by side in a high incidence worldwide. They are primarily caused by the significant overlap of microvascular and macrovascular aberrations, as well as several other factors, making them closely related to one another. A better understanding between these two is needed. This study examined the clinical profile of hypertension in DM patients at Surya Melati Muhammadiyah Hospital, Kediri, Indonesia, in 2021. Methods: This study employed an observational, descriptive design. The population of the study was patients with DM and hypertension treated at Surya Melati Muhammadiyah Hospital, Kediri, Indonesia, in 2021. This study used a total sampling method. Diabetes mellitus, hypertension, age, and gender were the observed variables. All the necessary data were obtained from the patients’ medical records. All statistical data analyses were conducted using Microsoft Excel. Results: A total of 520 DM patients were included, comprising 185 males and 335 females. Most of them were between 51 and 60 years old, with a total of 233 patients. A total of 277 DM patients with hypertension were included, comprising 89 males and 188 females. Most of them were between 51 and 60 years old, with a total of 121 patients. Conclusion: The number of diabetes mellitus patients with hypertension exceeded that of diabetes mellitus patients without hypertension. There were more female patients than males. Most of them were elderly.